Strategi Positioning Bantul Radio 89,1 FM sebagai radio masyarakat Bantul. - Rohanisya Marthanti (Jurusan Ilmu Komunikasi, 2013)
Krisna Mulawarman, S.Sos., M.Sn. Zein Mufarrih Muktaf, S.IP., M.Si, Budi Dwi Arifianto, S.Sn., M.Sn,